Gold nanorod / dendritic cuprous oxide composite particle as well as preparation method and application thereof
By modifying the gold nanorods and controlling the dendritic structural morphology of cuprous oxide, the problem of difficult to efficiently synthesize gold nanorods/deneddritic cuprous oxide composite particles in the prior art is solved, and the photocatalytic performance is significantly improved.
Patent Information
- Application Number
- CN202411909401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
It is difficult to efficiently synthesize gold nanorod/dendritic cuprous oxide composite particles with different sizes and morphology, and their photocatalytic performance has not been effectively improved.
The gold nanorods are modified by CTAB and dendritic copper oxide grow at a fixed point on their surface. The injection speed and stirring speed of hydrazine hydrate are controlled to regulate the dendritic structural morphology of cuprous oxide.
The efficient synthesis of gold nanorod/dendritic cuprous oxide composite particles with different sizes and morphology has been achieved, significantly improving their photocatalytic properties, especially in the rate of degradation of methyl orange solutions.
Smart Images

Figure CN119747649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a gold nanorod / dendritic cuprous oxide composite particle and a preparation method and application thereof. Background Art
[0002] Among the noble metals, gold, especially gold nanoparticles, have been widely used in photocatalysis, imaging, sensing, drug delivery and targeted therapy due to their fascinating optical properties, known as localized surface plasmon resonance (LSPR). It is well known that the LSPR performance of gold nanocrystals depends on their size, shape and morphology. For example, the LSPR peak of gold nanorods red-shifts with the increase of aspect ratio, so that they can better absorb light. As a P-type semiconductor, cuprous oxide (Cu2O) has the advantages of good crystallinity, good absorption of visible light, low toxicity and low cost. Therefore, gold nanorods can improve their photocatalytic performance after combining with dendritic cuprous oxide, because their catalytic activity can be significantly improved by the formation of Schottky barriers and the increase of surface area. Secondly, the special structure enables better charge separation, which can be applied to dye degradation. Secondly, due to the novel morphology of the gold nanorods / dendritic cuprous oxide, it can serve as an ideal model to study the growth mechanism of gold and semiconductor composites, and an ideal probe, carrier or marker in photocatalysis and various biomedical studies related to cellular uptake, drug delivery and biodistribution / targeting efficacy.
[0003] Gold nanorod / dendritic cuprous oxide has attracted extensive attention due to its unique morphology and composite structure, as well as its related optical properties. Therefore, in order to explore its properties and realize practical applications, it is crucial to control the synthesis of gold nanorod / dendritic cuprous oxide composite particles. Summary of the invention
[0004] The purpose of the present invention is to provide a gold nanorod / dendritic cuprous oxide composite particle and a synthesis method thereof. The method is simple, easy to implement, has a short reaction time and easily controllable reaction conditions; requires a small amount of reactants, has a low cost, and does not cause waste of resources; can efficiently synthesize gold nanorod / dendritic cuprous oxide composite particles with different sizes, and finally verify the rate of the gold nanorod / dendritic cuprous oxide composite particles in degrading a methyl orange solution.
[0005] The invention provides a gold nanorod / dendritic cuprous oxide composite particle and a synthesis method thereof. The synthesized gold nanorod / dendritic cuprous oxide composite particle has a novel morphology and good uniformity, and provides a more superior condition for improving the photocatalytic performance of the composite material. First, a gold nanorod modified with CTAB is prepared, and when the synthesized gold nanorod is added to a copper nitrate solution, copper ions are attached to the surface of the gold nanorod. The subsequent hydrazine hydrate will quickly reduce the copper ions to cuprous oxide particles, and the injection speed and stirring speed of the hydrazine hydrate are controlled to control the rate of copper ion reduction, so that the reaction is slower, and the cuprous oxide has a dendritic morphology. Finally, the synthesized gold nanorod / dendritic cuprous oxide composite particles are dispersed and stored in ethanol by washing and centrifugation.
[0006] The present invention provides a method for preparing gold nanorod / dendritic cuprous oxide composite particles, comprising the following steps:
[0007] S1, using surfactant CTAB to modify the gold nanorods. Due to the difference in curvature between the two ends and the middle part of the gold nanorods, the surfactant CTAB coated on the two ends of the gold nanorods is significantly less than that in the middle of the gold nanorods, thereby obtaining a CTAB-modified gold nanorod solution;
[0008] S2, obtaining a copper nitrate solution having a concentration range of 0.16 mM to 0.32 mM and a hydrazine hydrate solution having a concentration of 25%;
[0009] S3. Using the masking effect of CTAB modified on the gold nanorods, dendritic cuprous oxide is fixedly grown on both ends of the gold nanorods: after mixing a 32 volume fraction of copper nitrate solution with a 0.3 volume fraction of CTAB-modified gold nanorod solution, under stirring, slowly add a 0.2-0.5 volume fraction of hydrazine hydrate solution to reduce the copper nitrate to obtain gold nanorod / dendritic cuprous oxide composite particles.
[0010] Preferably, in S1, the use of surfactant CTAB to modify the gold nanorods specifically includes: adding a surfactant CTAB solution to the gold nanorods, so that the gold nanorods are stored in a CTAB solution with a concentration range of 0.7mM to 1mM, and based on the difference in surface curvature of the gold nanorods, the CTAB is unevenly coated on the surface of the gold nanorods.
[0011] Preferably, in S1, the gold nanorods are gold nanorods with a LSPR peak at 820 nm.
[0012] Preferably, in S3, the slowly adding of 0.2 to 0.5 volume fraction of hydrazine hydrate solution specifically comprises: using an injection feeding method, injecting 10% to 25% of the volume of the total hydrazine hydrate solution into the reaction system per minute.
[0013] Preferably, in S3, the length of the dendrites in the dendritic cuprous oxide is adjusted by controlling the concentration of the copper nitrate solution, and the specific adjustment method includes:
[0014] In the range of the concentration of the copper nitrate solution from 0.16 mM to 0.32 mM, the length of the dendrites increased as the concentration increased, and the length of the dendrites decreased as the concentration decreased.
[0015] The invention also provides gold nanorod / dendritic cuprous oxide composite particles prepared by the above preparation method.
[0016] The present invention also provides the gold nanorod / dendritic cuprous oxide composite particles for use in degrading methyl orange, comprising the following steps: adding sodium borohydride and the gold nanorod / dendritic cuprous oxide composite particles to a methyl orange solution, mixing them evenly, and then subjecting them to light treatment, wherein the gold nanorod / dendritic cuprous oxide composite particles serve as photocatalysts.
[0017] Beneficial effects of the present invention:
[0018] (1) The method is simple and easy to implement, the reaction time is short and the reaction conditions are easy to control; the amount of reactants required is small, the cost is low, and there is no waste of resources.
[0019] (2) The final product of the present invention, the gold nanorod / dendritic cuprous oxide composite particles, has high dispersibility, which helps to improve the photocatalytic performance.
[0020] (3) The final product of the present invention is the gold nanorod / dendritic cuprous oxide composite particles. By adding different volumes of copper nitrate and hydrazine hydrate, the dendritic structure morphology of cuprous oxide can be controlled. This provides ideas for the composite of metal and semiconductor materials, and has corresponding applications in photocatalysis and biomedical research. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a TEM image of the gold nanorod / dendritic cuprous oxide composite particles with a short dendritic structure according to Example 1 of the present invention.
[0022] Figure 2 This is a TEM image of the gold nanorod / dendritic cuprous oxide composite particles with a long dendritic structure according to Example 2 of the present invention.
[0023] Figure 3 This is a TEM image of the gold nanorod / cubic cuprous oxide composite particles with a cubic structure according to Example 3 of the present invention.
[0024] Figure 4 This is a TEM image of the gold nanorod / cuprous oxide composite particles with a core-shell structure according to Comparative Example 1 of the present invention.
[0025] Figure 5Spectra of the gold nanorods / cuprous oxide composite particles of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention.
[0026] Figure 6 This is a spectrum diagram of the synthetic product of Example 1 of the present invention used for photodegradation of methyl orange.
[0027] Figure 7 This is a spectrum diagram of the synthetic product of Example 2 of the present invention used for photodegradation of methyl orange.
[0028] Figure 8 This is a spectrum diagram of the synthetic product of Example 3 of the present invention used for photodegradation of methyl orange.
[0029] Fig. 9 This is a spectrum diagram of the synthetic product of Comparative Example 1 of the present invention used for photodegradation of methyl orange.
[0030] Fig.10 Graph showing the photocatalytic rates of the gold nanorod / cuprous oxide composite particles of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The invention discloses a gold nanorod / dendritic cuprous oxide composite particle and a synthesis method thereof, comprising the following steps:
[0032] S1: Preparation of initial CTAB-modified gold nanorods:
[0033] S10: Synthesize gold nanorods with an LSPR peak at 820 nm. The final product is centrifuged at 8000 rpm for 20 min, the supernatant is removed, and then ultrapure water is added for washing. The product after centrifugation and washing twice is dispersed in a certain concentration of surfactant CTAB, and the volume is 1 / 10 of that before centrifugation and washing.
[0034] S2: preparing a low concentration copper nitrate solution, wherein the concentration of the copper nitrate solution is 0.16 mM to 0.32 mM;
[0035] S20: Take a certain mass of copper nitrate solid and add a certain volume of ultrapure water, mix in a 40 ml glass bottle to form a copper nitrate solution;
[0036] S3: Preparation of hydrazine hydrate solution:
[0037] S30: Add a certain volume of hydrazine hydrate to ultrapure water, the volume ratio of the two is 3:1, and the concentration of hydrazine hydrate solution is 25%;
[0038] S4: Preparation of gold nanorods / dendritic cuprous oxide composite particles with dendritic structure:
[0039] S40: adding the gold nanorods obtained in S10 to the copper nitrate solution obtained in S20, stirring and mixing at a certain speed;
[0040] S41: During stirring, a certain volume of hydrazine hydrate solution is injected into the mixed solution obtained in S40 at a certain speed to mix;
[0041] S42: centrifuging the final product, gold nanorod / dendritic cuprous oxide composite particles, washing, and re-dispersing in ethanol;
[0042] S5: Preparation of methyl orange solution:
[0043] S50: Take a certain mass of methyl orange solid and add a certain volume of ultrapure water, and mix them in a certain volume of cuvette;
[0044] S6: Photocatalytic degradation of methyl orange:
[0045] S61: taking a certain volume of the solution obtained in S42, centrifuging it, washing it, and dispersing it in the solution obtained in S50 and mixing it thoroughly;
[0046] S62: Add a certain volume of sodium borohydride solution and place the cuvette under a xenon lamp for irradiation;
[0047] S63: after irradiation for a certain period of time, the spectrum of the solution in S63 is measured and repeated a certain number of times;
[0048] S64: Processing the spectrum data, taking the intensity at the spectrum peak, i.e., 464 nm, and substituting it into the formula to calculate the slope obtained as the catalytic rate of the particle;
[0049] Preferably, in S10, the certain concentration is 0.7 mM to 1 mM, the concentration multiple is 10 times, and the aspect ratio of the gold nanorods is 4.12.
[0050] Preferably, in S20, the certain mass is 0.00093778 g to 0.00375112 g, and the certain volume is 32 ml.
[0051] Preferably, in S30, the certain volume is 0.5 ml.
[0052] Preferably, in S40, the certain speed is 500 rpm / min.
[0053] Preferably, in S41, the certain volume is 0.2 ml to 0.5 ml, and the certain speed is 0.05 ml / min.
[0054] Preferably, in S42, the washing method is centrifugation at 10000 rpm for 5 min, washing once with water and once with ethanol.
[0055] Preferably, in S50, the certain mass is 0.000049 g, and the certain volume is 1 ml;
[0056] Preferably, in S61, the certain volume is 10 μL;
[0057] Preferably, in S62, the certain volume is 0.1 ml;
[0058] Preferably, in S63, the certain time is 1 minute, and the certain number of times is 20 times;
[0059] Preferably, in S64, the formula is -Ln(C / C0);
[0060] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0061] Example 1
[0062] A: Preparation of initial CTAB encapsulated gold nanorods:
[0063] (1) Gold nanorods (length 103 nm, diameter 25 nm) with an aspect ratio of 4.12 were synthesized according to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771). The resulting product was centrifuged and washed at 8000 °C.
[0064] After centrifugation at a speed of rpm for 20 min, the supernatant was removed, ultrapure water was added for washing, and the centrifugation washing was repeated twice. After that, the mixture was dispersed in CTAB with a concentration of 0.75 mM, and the volume was 1 / 10 of the volume before centrifugation washing.
[0065] B: Preparation of gold nanorods / dendritic cuprous oxide composite particles:
[0066] (1) Take 0.3 ml of CTAB-modified gold nanorod solution and mix it with copper nitrate solution (0.16 mM, 32 ml) in a 40 ml glass bottle.
[0067] (2) At 27°C, 0.25 ml of 25% hydrazine hydrate solution was injected into the glass bottle at a rate of 0.05 ml / min, and the mixture was stirred continuously at a rate of 500 rpm / min.
[0068] (3) The product was collected, centrifuged at 10,000 rpm for 5 min, washed with ethanol, and finally dispersed in an ethanol solution.
[0069] C: Photodegradation of methyl orange:
[0070] (1) Mix the gold nanorods / dendritic cuprous oxide composite particles with methyl orange solution (1 ml, 0.15 mM) in a cuvette.
[0071] (2) Add sodium borohydride solution (0.1 ml, 50 mM) into the cuvette and measure the solution spectrum after irradiation with a xenon lamp for 1 min.
[0072] (3) After repeating step C(2) 20 times, the obtained spectrum is processed and the extinction intensity at a wavelength of 464 nm is taken. The slope calculated by the formula -Ln(C / C0) is regarded as the catalytic rate of the composite particle.
[0073] Figure 1 This is a TEM image of the synthesized short dendritic gold nanorod / dendritic cuprous oxide composite particles of the present invention. The synthesized particles show a dendritic morphology with an anisotropic structure, and the synthesis time is relatively short. Figure 6 This is the photodegradation spectrum of methyl orange of the short dendritic gold nanorod / dendritic cuprous oxide composite particles synthesized by the present invention. Fig.10 This is a graph of the photocatalytic rate of the short dendritic gold nanorod / dendritic cuprous oxide composite particles synthesized by the present invention. The catalytic rate of the composite particles in Example 1 is 4 times that of Comparative Example 1.
[0074] Example 2
[0075] The difference between Example 2 and Example 1 is that the amount of copper nitrate is increased in step B (2), and on this basis, gold nanorods / dendritic cuprous oxide composite particles with larger diameters are synthesized.
[0076] A: Preparation of initial CTAB encapsulated gold nanorods:
[0077] (1) Gold nanorods (length 103 nm, diameter 25 nm) with an aspect ratio of 4.12 were synthesized according to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771). The resulting product was centrifuged at 8000 rpm for 20 min, the supernatant was removed, ultrapure water was added for washing, the centrifugation was repeated twice, and the product was dispersed in 0.75 mM CTAB in a volume of 1 / 10 of the volume before centrifugation.
[0078] B: Preparation of gold nanorods / dendritic cuprous oxide composite particles:
[0079] (1) Take 0.3 ml of CTAB-encapsulated gold nanorod solution and mix it with copper nitrate solution (0.32 mM, 32 ml) in a 40 ml glass bottle.
[0080] (2) At 27°C, 0.25 ml of 25% hydrazine hydrate solution was injected into the glass bottle at a rate of 0.05 ml / min, and the mixture was stirred continuously at a rate of 500 rpm / min.
[0081] (3) The product was collected, centrifuged at 10,000 rpm for 5 min, washed with ethanol, and finally dispersed in an ethanol solution.
[0082] C: Photodegradation of methyl orange:
[0083] (1) Mix the gold nanorods / dendritic cuprous oxide composite particles with methyl orange solution (1 ml, 0.15 mM) in a cuvette.
[0084] (2) Add sodium borohydride solution (0.1 ml, 50 mM) into the cuvette and measure the solution spectrum after irradiation with a xenon lamp for 1 min.
[0085] (3) After repeating step C(2) 20 times, the obtained spectrum is processed and the extinction intensity at a wavelength of 464 nm is taken. The slope calculated by the formula -Ln(C / C0) is regarded as the catalytic rate of the composite particle.
[0086] Figure 2 This is a TEM image of the synthesized long dendritic gold nanorod / dendritic cuprous oxide composite particles of the present invention. The synthesized particles show excellent uniformity and special morphology. Figure 7 This is the photodegradation spectrum of methyl orange of the long dendritic gold nanorod / dendritic cuprous oxide composite particles synthesized by the present invention. Fig.10 This is a graph of the photocatalytic rate of the long dendritic gold nanorod / dendritic cuprous oxide composite particles synthesized by the present invention. The catalytic rate of the composite particles in Example 2 is 7 times that of Comparative Example 1.
[0087] Example 3
[0088] The difference between Example 3 and Example 2 is that the amount of copper nitrate is increased in step B(2), thereby synthesizing gold nanorods / cubic cuprous oxide composite particles having a cubic shape.
[0089] A: Preparation of initial CTAB encapsulated gold nanorods:
[0090] (1) Gold nanorods (length 103 nm, diameter 25 nm) with an aspect ratio of 4.12 were synthesized according to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771). The resulting product was centrifuged at 8000 rpm for 20 min, the supernatant was removed, ultrapure water was added for washing, the centrifugation was repeated twice, and the product was dispersed in 0.75 mM CTAB in a volume of 1 / 10 of the volume before centrifugation.
[0091] B: Preparation of gold nanorods / cubic cuprous oxide composite particles:
[0092] (1) Take 0.3 ml of CTAB-encapsulated gold nanorod solution and mix it with copper nitrate solution (0.64 mM, 32 ml) in a 40 ml glass bottle.
[0093] (2) At 27°C, 0.25 ml of 25% hydrazine hydrate solution was injected into the glass bottle at a rate of 0.05 ml / min, and the mixture was stirred continuously at a rate of 500 rpm / min.
[0094] (3) The product was collected, centrifuged at 10,000 rpm for 5 min, washed with ethanol, and finally dispersed in an ethanol solution.
[0095] C: Photodegradation of methyl orange:
[0096] (1) Mix the gold nanorods / cubic cuprous oxide composite particles with methyl orange solution (1 ml, 0.15 mM) in a cuvette.
[0097] (2) Add sodium borohydride solution (0.1 ml, 50 mM) into the cuvette and measure the solution spectrum after irradiation with a xenon lamp for 1 min.
[0098] (3) After repeating step C(2) 20 times, the obtained spectrum is processed and the extinction intensity at a wavelength of 464 nm is taken. The slope calculated by the formula -Ln(C / C0) is regarded as the catalytic rate of the composite particle.
[0099] Figure 3 This is a TEM image of the gold nanorod / cubic cuprous oxide composite particles synthesized in the present invention with a cubic morphology. The synthesized particles show excellent uniformity and a special morphology of anisotropic structure. Figure 8 This is the photodegradation spectrum of methyl orange of the gold nanorod / cubic cuprous oxide composite particles synthesized in the present invention. Fig.10 This is a graph of the photocatalytic rate of the cubic gold nanorod / cubic cuprous oxide composite particles synthesized by the present invention. The catalytic rate of the composite particles in Example 3 is 2.4 times that of Comparative Example 1.
[0100] Comparative Example 1
[0101] The difference between Comparative Example 1 and Example 2 is that in step B(2), the hydrazine hydrate solution is injected once during the synthesis process, resulting in the synthesized cuprous oxide particles having no dendritic morphology.
[0102] A: Preparation of initial CTAB encapsulated gold nanorods:
[0103] (1) Gold nanorods (length 103 nm, diameter 25 nm) with an aspect ratio of 4.12 were synthesized according to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771). The resulting product was centrifuged at 8000 rpm for 20 min, the supernatant was removed, ultrapure water was added for washing, the centrifugation was repeated twice, and the product was dispersed in 0.75 mM CTAB in a volume of 1 / 10 of the volume before centrifugation.
[0104] B: Preparation of gold nanorods / cuprous oxide composite structure:
[0105] (1) Take 0.3 ml of CTAB-encapsulated gold nanorod solution and mix it with copper nitrate solution (0.32 mM, 32 ml) in a 40 ml glass bottle.
[0106] (2) At 27°C, inject 0.25 ml of 25% hydrazine hydrate solution into the glass bottle at one time and continue stirring at a speed of 500 rpm / min.
[0107] (3) The product was collected, centrifuged at 10,000 rpm for 5 min, washed with ethanol, and finally dispersed in an ethanol solution.
[0108] C: Photodegradation of methyl orange:
[0109] (1) Mix gold nanorods / cuprous oxide composite particles and methyl orange solution (1 ml, 0.15 mM) in a cuvette.
[0110] (2) Add sodium borohydride solution (0.1 ml, 50 mM) into the cuvette and measure the solution spectrum after irradiation with a xenon lamp for 1 min.
[0111] (3) After repeating step C(2) 20 times, the obtained spectrum is processed and the extinction intensity at a wavelength of 464 nm is taken. The slope calculated by the formula -Ln(C / C0) is regarded as the catalytic rate of the composite particle.
[0112] Figure 4 This is a TEM image of gold nanorod / cuprous oxide composite particles with a core-shell structure synthesized by the present invention. The synthesized particles have a chaotic morphology, do not have the characteristics of anisotropic structure, and have poor uniformity. Fig. 9 This is the photodegradation spectrum of methyl orange of the gold nanorod / cuprous oxide composite particles with a core-shell structure synthesized by the present invention. Fig.10 This is a diagram of the photocatalytic rate of the gold nanorod / cuprous oxide composite particles with a core-shell structure synthesized by the present invention. The catalytic rate of the gold nanorod / cuprous oxide composite particles with a core-shell structure is the slowest.
[0113] Finally, it should be noted that the above embodiments are only used to help understand the method of the present invention and its core ideas, rather than to limit them. Those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the device solution of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing gold nanorod / dendritic cuprous oxide composite particles, characterized in that: The following steps are involved: S1, using surfactant CTAB to modify the gold nanorods. Due to the difference in curvature between the two ends and the middle part of the gold nanorods, the surfactant CTAB coated on the two ends of the gold nanorods is significantly less than that in the middle of the gold nanorods, thereby obtaining a CTAB-modified gold nanorod solution; S2, obtaining a copper nitrate solution having a concentration range of 0.16 mM to 0.32 mM and a hydrazine hydrate solution having a concentration of 25%; S3. Using the masking effect of CTAB modified on the gold nanorods, dendritic cuprous oxide is fixedly grown on both ends of the gold nanorods: after mixing a 32 volume fraction of copper nitrate solution with a 0.3 volume fraction of CTAB-modified gold nanorod solution, under stirring, slowly add a 0.2-0.5 volume fraction of hydrazine hydrate solution to reduce the copper nitrate to obtain gold nanorod / dendritic cuprous oxide composite particles.
2. The method for preparing a gold nanorod / dendritic cuprous oxide composite particle according to claim 1, characterized in that: In S1, the use of surfactant CTAB to modify the gold nanorods specifically includes: adding a surfactant CTAB solution to the gold nanorods, so that the gold nanorods are stored in a CTAB solution with a concentration range of 0.7mM to 1mM, and based on the difference in surface curvature of the gold nanorods, the CTAB is unevenly coated on the surface of the gold nanorods.
3. The method for preparing a gold nanorod / dendritic cuprous oxide composite particle according to claim 1, characterized in that: In S1, the gold nanorods are gold nanorods with a LSPR peak at 820 nm.
4. The method for preparing a gold nanorod / dendritic cuprous oxide composite particle according to claim 1, characterized in that: In S3, the slowly adding of 0.2-0.5 volume fraction of hydrazine hydrate solution specifically comprises: using an injection feeding method, injecting 10%-25% of the volume of the total hydrazine hydrate solution into the reaction system per minute.
5. The method for preparing the gold nanorod / dendritic cuprous oxide composite particles according to claim 1, characterized in that: In S3, the length of the dendrites in the dendritic cuprous oxide is adjusted by controlling the concentration of the copper nitrate solution. The specific adjustment method includes: when the concentration of the copper nitrate solution is in the range of 0.16 mM to 0.32 mM, the length of the dendrites is increased by increasing the concentration, and the length of the dendrites is reduced by reducing the concentration.
6. Gold nanorod / dendritic cuprous oxide composite particles obtained by the preparation method according to any one of claims 1 to 5.
7. The gold nanorod / dendritic cuprous oxide composite particles as claimed in claim 6 are used to degrade methyl orange, characterized in that: The following steps are involved: Sodium borohydride and gold nanorod / dendritic cuprous oxide composite particles are added to a methyl orange solution, mixed evenly, and then subjected to light treatment, wherein the gold nanorod / dendritic cuprous oxide composite particles serve as a photocatalyst.